Book Reviews (The Muslim world, 1962)
Book reviewed in this article: Islam and the West. The Making of an Image. By Norman Daniel. The Mideast in Focus. By Norman Greenwald. Arabian Sands. By Wilfred Thesiger. The Black Muslims in America. By C. Eric Lincoln. The Intellectual Origins of Egyptian Nationalism. By Jamal Mohammed Ahmed. Sufism: Its Saints and Shrines. By John A. Subhan. Mishkät al-Masābih. English translation, with notes, by James Robson. Islamic Law and Constitution. By Abul Aclā Maudūd?, translated and edited by Khurshid Ahmad. 2nd ed.